Three‐Dimensional Numerical Simulation of Rime Ice Accretion on Polymeric Insulator Based on Computational Fluid Dynamics and its Experimental Verification - Zong, Chunyu; Hu, Yuyao; Jiang, Xingliang; Du, Qinjun; Rong, Qingyu; Geng, Kai (IEEJ transactions on electrical and electronic engineering, 2023)
Ice accretion on transmission lines seriously threaten the stable operation of power grid. The current research focuses on the discharge development and flashover characteristics of ice‐covered insulator. Due to the irregular structure of the insulator, very few studies concentrate on the mechanism of ice accumulation. In the present study, the local collision coefficient was determined, and then a three‐dimensional numerical model for rime ice deposit accumulation on polymeric insulator was established based on computational fluid dynamics and verified by experiments. Results show that the local collision efficiency decreases along the rod and the edge of the shed from the front stagnation point to both sides, whose maximum values are 0.73 and 0.74 in the research scope. Rime ice amount on the insulator increases with the increment of environmental parameters including wind velocity, liquid water content, and median volume diameter of water droplet. It was proved by numerical simulation and artificial tests that the position with a high collision efficiency is heavily covered with rime ice. Through comparison and analysis, the numerical model can well simulate the process of rime ice accretion on polymeric insulator, and the relative error of ice amount between calculated by the model and that obtained by the test is less than 18.8%. The research in this paper realizes the visualization of rime ice‐coating process of polymeric insulator. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.